The robustness of poverty profiles reconsidered - Tarp, Finn; Simler, Kenneth R.; Matusse, Cristina; Heltberg, Rasmus; Dava, Gabriel (International Food Policy Research Institute, 2002)
Poverty measures and profiles are used increasingly to guide antipoverty policies in low-income countries. An essential element in these analyses is the specification of a poverty line. However, there are many different methods for setting poverty lines, and different methods can yield strikingly different results, with correspondingly different policy implications. Using recent household survey data from Mozambique, this paper explores the differences that occur using the most common poverty line methodologies, the Food Energy Intake (FEI) and the Cost of Basic Needs (CBN) methods, over different levels of geographic specificity. We find that regional and provincial rankings of Foster, Greer, and Thorbecke poverty indices are not robust to the method of poverty line determination, but that the characteristics of the poor are reasonably similar under all methods. The FEI poverty lines often yield counterintuitive results, whereas the family of CBN poverty lines was more robust. Food consumption patterns of the poor show a high degree of substitution among basic staples from one region to another, which is consistent with observed differences in relative food prices, indicating that CBN poverty lines that allow for regional variation in the food consumption bundle may be most appropriate in these settings.